2016
DOI: 10.1007/s11069-016-2341-x
|View full text |Cite
|
Sign up to set email alerts
|

Advanced interpretation of interferometric SAR data to detect, monitor and model ground subsidence: outcomes from the ESA-GMES Terrafirma project

Abstract: Land subsidence is a common natural hazard striking extensive areas worldwide, with severe impacts on economy and environment. Subsidence has been recognized as one of geohazards needing research efforts and knowledge transfer at international level, especially when urban fabrics and infrastructures are directly involved in the land settling. Policies and solutions for land subsidence management can be different. Despite this variability, where mitigation methods need to be adopted, mapping, monitoring and sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 52 publications
0
14
0
1
Order By: Relevance
“…11 relevant to the Fiumicino Airport and surroundings (Southwest of the urban area of Rome, in central Italy). In this case, the map reveals a spatially extended subsidence pattern related to the interaction between natural and man-induced causes, i.e., compaction of unconsolidated sediments and progressive urbanization [82]. The observed deformation pattern is characterized by a deformation rate up to 2 cm/year, clearly shown by the temporal evolution of the displacement reported for the pixel labeled as P2 and identified with a black star in Fig.…”
Section: B Processing Chain Results Quality Assessmentmentioning
confidence: 80%
“…11 relevant to the Fiumicino Airport and surroundings (Southwest of the urban area of Rome, in central Italy). In this case, the map reveals a spatially extended subsidence pattern related to the interaction between natural and man-induced causes, i.e., compaction of unconsolidated sediments and progressive urbanization [82]. The observed deformation pattern is characterized by a deformation rate up to 2 cm/year, clearly shown by the temporal evolution of the displacement reported for the pixel labeled as P2 and identified with a black star in Fig.…”
Section: B Processing Chain Results Quality Assessmentmentioning
confidence: 80%
“…The study area, located in the municipalities of Rome and Fiumicino (Italy), is affected by important subsidence phenomena [23], features a high geological and geotechnical variability, and has been built upon for approximately 100 years. Moreover, in the region, a large urban expansion is in progress and additional expansion is already planned.…”
Section: Introductionmentioning
confidence: 99%
“…In cases where elevation rapidly decreases and considering the fact that those buildings are predominantly one-to two-storey residential dwellings, it can be easily concluded that they are largely exposed to impact from heavy rain and flooding events. This is a typical phenomenon in many southern European cities [39].…”
Section: Exposure Of the Built Environmentmentioning
confidence: 86%
“…Lastly, it is worth recalling that the intensification of industrial development and agricultural activities and the consequent increasing water demand have recently led to overexploitation of local aquifers and amplification of compaction of compressible deposits and ground subsidence phenomena, further increasing the geological vulnerability of Perea [34,39]. In a scenario of increasing groundwater overexploitation of the aquifer system in the coastal zone of Thermaikos Municipality, land subsidence may become a further threat, principally in those areas where Quaternary alluvial formations are thick, with a lowering of the ground level.…”
Section: Geological Vulnerabilitymentioning
confidence: 99%